PENGARUH KOMPENSASI, KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PENDIDIK DI LEMBAGA KURSUS DAN PELATIHAN LADIKA - Asep Tantula (Universitas Mercu Buana, 2013)
Abstract: This research examined the effect of compensation, competency, andmotivation on the performance of acupuncture teachers in LKP Ladika. This researchused quantitative approach with descriptive survey method. Data were taken usingquestionnaires. Data were analyzed using SPSS. Methods of data analysis in thisresearch were multiple linear regression analysis with the classical assumption test,such as normality test and multicollinearity test. At the multiple regression analysis willbe shown descriptive statistics, correlation test, determination test, t test and F test. Theresults of this research shown that compensation, competency and motivationaltogether had significant influence toward those performance of acupuncture teachersin LKP Ladika. Partially, only the variable of competency had statistical significantefeect to their performance.Keywords: Compensation, Competency, Motivation, Performance